Experience of being a family caregiver in childhood cancer - Silva, Talitha Carneiro de Oliveira; Barros, Viviane Farias; Hora, Edilene Curvelo (Rev Rene, 2011)
The aim of this study was to describe the experience of a family caregiver of a child with cancer. A qualitative and descriptive study was carried out at a Center of Oncology in Sergipe — Brazil, from January to May, 2008. In order to collect data it was used an open interview containing the main question: What has it been like to treat children with cancer? The sample consisted of 19 caregivers. The method of content analysis proposed was chosen and, as a result, four categories were obtained. The following categories were found: A hard Journey, the impact on the caregiver’s life and family, the support on care and expectations for the future. Even though the diagnosis of childhood cancer in the perspective of the caregiver has been proved to be a hard, painful and even helpless experience, with impact on his life and family dynamics, there are still some positive expectations for the future.